School-Based Nonformal Learning Support for Slow Learners: A Case Study of the Talent Optimizing Program in History Education - Agustinova, Danu Eko; Sakiakirti, Gadis; Abdullah, Rabaah Binti (Journal of Nonformal Education, 2026)
Background: The significance of employing innovative methods in teaching history to slow learners is crucial, particularly within inclusive education settings. The Talent Optimizing Program (TOP) serves as a supportive initiative for these students while also highlighting gaps in teachers’ preparedness to effectively address students’ diverse needs, especially in subjects like history that require advanced cognitive skills. Research Objective: This study aims to analyze and describe the strategies and implementation of history instruction for slow learners in inclusive schools, identify challenges stemming from mismatched educational backgrounds of history teachers, and assess the learning achievements of slow learners through the TOP program. Research Methodology: The research adopted a descriptive qualitative approach, involving participants such as history teachers, TOP coordinators, principals, and grade X slow learners at SMK Budi Mulia Dua Yogyakarta. Data collection techniques included observation, interviews, and document analysis. To ensure data validity, both source and technique triangulation were employed. Data analysis followed the Miles and Huberman model, encompassing data collection, reduction, presentation, and conclusion drawing. Research Result: Findings indicated that history instruction for slow learners at SMK Budi Mulia Dua Yogyakarta is conducted through an individualized approach utilizing the TOP, with the development of personalized Learning Plans (RPI) tailored to each student’s needs. This approach enhanced students’ comprehension, social interactions, and independence, despite challenges related to teachers’ educational backgrounds and limited learning resources. Research Conclusion: The successful history learning for slow learners at SMK Budi Mulia Dua Yogyakarta underscores the importance of inclusive, personalized learning strategies and highlights the necessity for ongoing support for teachers to improve teaching quality and effectiveness in the future. Research Novelty/ Constribution: Applying the Talent Optimizing Program (TOP) specifically to history instruction for slow learners in an inclusive vocational-school setting. While TOP has been used in other subjects, this is among the first investigations of its impact on a cognitively demanding topic like history.